Determinación De Las Características Anatómicas De Las Arterias Coronarias En El Gato Doméstico (Felis Catus) Mediante Técnicas De Inyección Vascular (2023)
A significant increase in pet ownership is booming, cats and dogs as pets. company represent the largest number in this trend. Diseases that affect these species They are diverse and significant studies in the different areas of knowledge of veterinary medicine. They are necessary to counteract the pathologies they present. Anatomy as a science, establishes the bases for other subjects such as physiology and pathology, therefore, this study developed in the domestic cat determined through an anatomical vascular repression technique with neoprene latex in two bodies; that the vascular pattern of the heart is similar to that reported in the dog.